Penerapan model pembelajaran kooperatif tipe make a match untuk meningkatkan aktivitas dan hasil belajar akidah akhlak pada materi indahnya Al-Asmaa Al-Husna kelas IV MIN 10 Aceh besar - Salmawati, Salmawati (Jurnal Pendidikan dan Pengabdian Vokasi (JP2V), 2020)
The purpose of this study was to improve the activities and learning outcomes of the Islamic creed on the beauty of al-asmaa al-husna through the type of make a match cooperative learning model class IV MIN 10 Aceh Besar in the academic year 2018/2019. The learning model used in this classroom action research is a make a match type of cooperative learning model. The subjects of this classroom action research were students in class IV MIN Aceh Besar. The number of students is 25 students with 13 male students and 12 female students. This class action research was conducted in the 2018/2019 school year. This class action research was conducted in a period of 3 months, from July 2018 to September 2018 in odd semester. The methodology of this research is classroom action research consisting of two cycles and each cycle consists of two meetings. In each cycle consists of planning, implementation, observa-tion and reflection. The research procedure consisted of pre-research, planning cycle one, implementing cycle one, observing cycle one, reflection cycle one, planning cycle two, implementing cycle action two, observing cycle two and reflection cycle two. Data collection techniques were performed using tests, observation of teacher skills, observation of student activities and student questionnaire responses. Test scores are carried out at the end of each lesson in each cycle using the question instrument (written test). Observation data is done by looking at student activity and teacher skills in the learning process. Student response data obtained through a questionnaire. Data were analyzed using percentage descriptive statis-tics. The results showed that: 1) an increase in completeness of student learning outcomes from 52% in pre-study increased to 68% in the first cycle and increased to 92% in the second cycle. 2) Teacher skills have increased from 76% and increased to 88% 3) Student learning activities have increased from 76.67% and increased to 93.33%, 4) Positive student responses to teaching and learning activities using the make type cooperative learning model a match. Then it can be concluded that through the application of the make a match type of cooperative learning model increases the activities and learning outcomes of the Morals of the fourth grade students of MIN 10 Aceh Besar in the year